Medicine, religion, and the body - Coleman, Elizabeth Burns, 1961-; White, Kevin, PhD. (Leiden ; Boston : Brill, 2010)
This book develops an interdiscplinary as well as cross cultural and historical analyses of the relationship between medicine, religion, and the body.
Acknowledgments -- Contributors -- 1. The Social and Spiritual Body -- 2. Negotiating Medicine, Healing and Religious Belief -- 3. Virtue, Health and the State -- Bibliography -- Index.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 650
Keywords: Medicine -- Religious aspects; Human body -- Religious aspects; Human Body; Religion and Medicine; RELIGION -- Christianity -- General; BODY, MIND & SPIRIT -- Gaia & Earth Energies; Human body -- Religious aspects; Medicine -- Religious aspects; Heilung; Körper; Kulturvergleich; Religion; Medizin; Geistheilung; Leiblichkeit; Electronic books